Luminosity functions of cluster galaxies. The near-ultraviolet luminosity function at < z > ∼ 0.05 - Robert De Propris; Malcolm N Bremer; Steven Phillipps (EDP SCIENCES S A, 2022)
We derive NUV luminosity functions for 6471 NUV detected galaxies in 28 0.02 < z < 0.08 clusters and consider their dependence on cluster properties. We consider optically red and blue galaxies and explore how their NUV LFs vary in several cluster subsamples, selected to best show the influence of environment. Our composite LF is well fit by the Schechter form with M*(NUV) = -18.98 +/- 0.07 and alpha = -1.87 +/- 0.03 in good agreement with values for the Coma centre and the Shapley supercluster, but with a steeper slope and brighter L* than in Virgo. The steep slope is due to the contribution of massive quiescent galaxies that are faint in the NUV. There are significant differences in the NUV LFs for clusters having low and high X-ray luminosities and for sparse and dense clusters, though none are particularly well fitted by the Schechter form, making a physical interpretation of the parameters difficult. When splitting clusters into two subsamples by X-ray luminosity, the ratio of low to high NUV luminosity galaxies is higher in the high X-ray luminosity subsample (i.e., the luminosity function is steeper across the sampled luminosity range). In subsamples split by surface density, when characterised by Schechter functions the dense clusters have an M* about a magnitude fainter than that of the sparse clusters and alpha is steeper (-1.9 vs. -1.6, respectively). The differences in the data appear to be driven by changes in the LF of blue (star-forming) galaxies. This appears to be related to interactions with the cluster gas. For the blue galaxies alone, the luminosity distributions indicate that for high L-X and high velocity dispersion cluster subsamples (i.e., the higher mass clusters), there are relatively fewer high UV luminosity galaxies (or correspondingly a relative excess of low UV luminosity galaxies) in comparison the lower mass cluster subsamples.